Modulatory ATP binding to the E2 state of maize plasma membrane H+‐ATPase indicated by the kinetics of vanadate inhibition. (23rd August 2013) - Wang, Xiaozhi; Qian, Xiaoqing; Stumpf, Beate; Fatima, Ammara; Feng, Ke; Schubert, Sven; Hanstein, Stefan
<x xml:space="preserve">Abstract</x> P‐type ATPases, as major consumers of cellular ATP in eukaryotic cells, are characterized by the formation of a phosphorylated enzyme intermediate (E2P), a process that is allosterically coupled to translocation of cations against an electrochemical gradient. The catalytic cycle comprises binding of Mg‐ATP at the nucleotide‐binding domain, phosphorylation of the E1 state (E1), conformational transition to the E2P state, and dephosphorylation through the actuator domain and re‐establishment of the E1 state. Recently, it has been suggested that, for several P‐type ATPases, Mg‐ATP binds to the phosphorylated enzyme, thereby accelerating the transition to the E1 state, before then becoming the enzyme's catalytic substrate. Here, we provide evidence supporting this viewpoint. We employed kinetic models based on steady‐state kinetics in the presence and absence of the reversible inhibitor orthovanadate. Vanadate is generally considered to be a conformational probe that specifically binds to the E2 state, arresting the enzyme in a state analogous to the E2P state. Hydrolytic H+‐ATPase activities were measured in inside‐out plasma membrane vesicles isolated from roots and shoots of maize plants. For root enzymes, kinetic models of vanadate inhibition that allow simultaneous binding of Mg‐ATP and vanadate to the same enzyme state were most plausible. For shoot enzymes, application of the competitive inhibitor Mg‐free ATP attenuated vanadate inhibition, which is consistent with a model in which either Mg‐free ATP or Mg‐ATP is bound to the enzyme when vanadate binds. Therefore, data from roots and shoots indicate that binding of ATP species before transition to the E1 state plays an important role in the catalytic cycle of plant plasma membrane H+‐ATPase.